Small Scale Genetic Population Structure of Coral Reef Organisms in Spermonde Archipelago, Indonesia - Timm, Janne; Kochzius, Marc; Madduppa, Hawis H.; Neuhaus, Anouk I.; Dohna, Tina (Frontiers in Marine Science, 2017)
Small island archipelagos with fringing and dispersed reef systems represent special marine ecosystems, providing a patchy habitat for many coral reef organisms. Although geographic distances may be short, it is still unclear if such environments are inhabited evenly with panmictic conditions or if limited connectivity between marine populations, even on small geographic scales, leads to genetic differentiation between areas within the archipelago or even single reef structures. To study diversity patterns and connectivity between reefs of the Spermonde Archipelago, Indonesia, population genetic analyses of two reef organisms were performed by using the mitochondrial control region and microsatellite markers. A vertebrate (clown anemonefish) and an invertebrate species (sea squirt) were studied in parallel to investigate if there are general patterns of connectivity in Spermonde for sessile or site attached marine species, which can be extrapolated to a larger group. The genetic population structures revealed restrictions in gene flow in the clown anemone fish (Amphiprion ocellaris), especially between near-shore reefs in the South of the archipelago. This indicates very localised genetic exchange and may also reflect the high self-recruitment typical for these fish. The northern reefs show higher connectivity despite geographic distances being larger. The filter-feeding sessile sea squirt, Polycarpa aurata, features similar population patterns, especially in the southern area. However, connectivity is generally higher in the middle and shelf edge areas of Spermonde for this species. The results underline that there are restrictions to gene flow even on very small geographic scales in the studied organisms, with many barriers to gene flow in the southern shallower shelf area. Weaker currents in this area may lead to more influence of biological factors for dispersal, such as larval behaviour, motility and competition for suitable habitat. The results are discussed in the context of conservation and MPA planning in the Spermonde Archipelago.